An excellent mystery : the eleventh chronicle of Brother Cadfael - Peters, Ellis, 1913-1995 (MysteriousPress.com/Open Road Integrated Media, Inc., 2021)
In the sunny month of August, A.D. 1141, Brother Cadfael is presented with a double mystery set against the larger drama enacted by King Stephen and his arch-enemy, cousin, and rival claimant to the throne, the Empress Maud. In the bloody struggle for the crown, Henry of Blois, Bishop of Winchester and papal legate, is drawn into a contretemps that will result in a town laid waste, a nunnery burned to the ground, churches razed, and the priory of Hyde Mead engulfed in flames. Hence the arrival of Brothers Humilis and Fidelis to the abbey of St. Peter and St. Paul at Shrewsbury. Humilis, the elder of the pair, has entered the cloister because of the profound injuries he suffered during the Crusades. His companion and friend is a retiring youth whose perfect devotion to Humilis is made all the more poignant by his muteness. Concerned with the fragile condition of Humilis's health, Cadfael comes to his assistance with his prodigious skills as an herbalist -- and as a friend. - Jacket flap.